2000
DOI: 10.1143/jjap.39.1044
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of InGaN Pattern Formation Caused by Phase Separation

Abstract: We performed a numerical study of the two-dimensional pattern formation of InGaN driven by a phase separation using the cell dynamical system (CDS) approach to reveal the detailed nature of a self-assembled InGaN dot-like structure showing characteristic optical properties. We calculated two-dimensional pattern formations under various conditions. First, over a wide In compositional range (0 < In < 0.6), a dot-like structure appears arising from a phase separation as well as due to the effects of strains and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In previous papers, 6,7 we also found that the diffusion of the constituents has a strong effect on the evolution rate in the phase separation, that is, on the width of the In compositional fluctuation at an early stage of phase separation. Furthermore, we noticed that it is very important to enhance the diffusion in order to obtain a spatially uniform In composition.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…In previous papers, 6,7 we also found that the diffusion of the constituents has a strong effect on the evolution rate in the phase separation, that is, on the width of the In compositional fluctuation at an early stage of phase separation. Furthermore, we noticed that it is very important to enhance the diffusion in order to obtain a spatially uniform In composition.…”
Section: Introductionmentioning
confidence: 54%
“…In a numerical study of InGaN-based light-emitting devices, this CDS simulation represents the process simulation of the phase separation during the growth of the InGaN active layer. 6,7 In the second step, we consider the two factors responsible for the time evolution of : ͑i͒ phase separation induced by the driving force due to the mixing free energy and ͑ii͒ compositional uniformity induced by the driving force due to the diffusion of the constituents denoted by a phenomenological diffusion constant D. For factor ͑i͒, we introduced the map f () for the transformation as the driving force arising from the mixing free energy ⌬G, as described by the single-cell dynamics. This map f should have the features provided by the bistability of ⌬G for InGaN.…”
Section: A Procedures and Parameters Used In Cdsmentioning
confidence: 99%
See 2 more Smart Citations